2005
DOI: 10.1002/ejoc.200400557
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of the [2+2] Cycloaddition of Chlorosulfonyl Isocyanate to Chiral Alkoxyallenes Derived from 1,3‐Alkylidene‐L‐erythritol and ‐D‐threitol

Abstract: The [2+2] cycloaddition of chlorosulfonyl isocyanate to alkoxyallenes derived from ethylidene and benzylidene erythritols and threitols proceeds with a moderate asymmetric induction in the case of the erythritols and with a very low induction in the case of threitols. This indicates that the erythritol derivatives may exist in solution in one predominant conformation while the threitol derivatives behave as a conformational ensemble. The conformations of alkoxyallenes were studied with variety of NMR technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…The rule was demonstrated experimentally to be correct for a variety of oxacephams. 8,9 It was also found that the same rule is valid for clavams. 10,11 This helicity rule for both oxacephams and clavams was established empirically on the basis of X-ray structures and the tentative assignment of the electronic transition at $220 (oxacephams) and 240 nm (clavams) to an np* amide transition in the azetidinone system.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The rule was demonstrated experimentally to be correct for a variety of oxacephams. 8,9 It was also found that the same rule is valid for clavams. 10,11 This helicity rule for both oxacephams and clavams was established empirically on the basis of X-ray structures and the tentative assignment of the electronic transition at $220 (oxacephams) and 240 nm (clavams) to an np* amide transition in the azetidinone system.…”
Section: Introductionmentioning
confidence: 64%
“…Most probably, however, the CD band represents a sum of contributions from the amide and benzene ( 1 L b ) chromophores present in these molecules. In the respective UV spectra, the electronic absorption of y The crystallographic data for structures 9 phenyl group is clearly visible at ca. 257 nm and possesses characteristic fine structure (Table 1).…”
Section: Results and Disscusion Experimental Uv And Ecd Spectra Of CLmentioning
confidence: 97%
“…The [2 þ 2] cycloaddition of chlorosulfonyl isocyanate (CSI) to alkoxyallenes derived from ethylidene and benzylidene erythritols and threitols proceeds with a moderate asymmetric induction in the case of the erythritols (Scheme 24.6) and with a very low induction in the case of threitols. This indicates that the erythritol derivatives may exist in solution in one predominant conformation while the threitol derivatives behave as a conformational ensemble [50].…”
Section: Isocyanate-alkene Cyclocondensationmentioning
confidence: 99%
“…碱催化体系(NaOH 或 EtONa/EtOH)下, 4-乙酰氧基 氮杂环丁酮同样可发生亲核取代离去乙酰基团, 缩合反 应闭环形成苯并氧头孢 [79,80] (Scheme 13). [107,108] , alkylidenecephalosporins [109] 等抗生素, 环外双键对其生物活性均产生 重要影响 [110] . (2) [138,139] .…”
Section: -乙烯氧基氮杂环丁酮的乙烯氧基在一定条件下unclassified